Financial Ramifications of Coronavirus on Division I Athletic Departments (Comparative & International Education Series, 2021)
In the spring of 2020, safety and health concerns with COVID-19 shut down college sports. Most notably, the National Collegiate Athletic Association’s basketball tournament, better known as March Madness, was canceled, costing the Association and its member institutions almost $1 billion. A common misconception concerning intercollegiate athletics is that most athletic departments generate revenue for their institutions. However, less than 30 of the 347 Division I athletic departments operate in the black. Thus, this loss of revenue has resulted in unprecedented financial issues and considerations, such as cutting sports, furloughing staff, and offering fewer support resources for athletes. Through the lens of resource dependence theory, this chapter offers a synthesis of the available literature and examines the financial ramifications of the coronavirus on Division I athletic department operations.How to cite this chapter:Harry, M. (2022). Financial ramifications of coronavirus on division I athletic departments. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 51-64). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/